2013
DOI: 10.1039/c3cp44278k
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the water–carbon interaction: molecular simulations of water in low-diameter carbon nanotubes

Abstract: Effective Lennard-Jones models for the water-carbon interaction are derived from existing high-level ab initio calculations of water adsorbed on graphene models. The resulting potential energy well (εCO + 2εCH ≈ 1 kJ mol(-1)) is deeper than most of the previously used values in the literature on water in carbon nanotubes (CNTs). Moreover, a substantial anisotropy of the water-carbon interaction (εCO ≈ 2εCH) is obtained, which is neglected in most of the literature. We systematically investigate the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 64 publications
3
46
0
Order By: Relevance
“…2 and 3) can be done by considering the presence of water. The study of Walther et al [30] and also of other authors [31,32] revealed the properties of water at the vicinity of closed carbon nanotubes. Water molecules, being located are at the distance 0.32 nm from nanotubes, have (in the first layer) two times larger density than bulk water, and are oriented with hydrogen atoms closer to nanotube than oxygen.…”
Section: Conclusion: Effect Of Curvature On Energetics Of Benzene Admentioning
confidence: 91%
“…2 and 3) can be done by considering the presence of water. The study of Walther et al [30] and also of other authors [31,32] revealed the properties of water at the vicinity of closed carbon nanotubes. Water molecules, being located are at the distance 0.32 nm from nanotubes, have (in the first layer) two times larger density than bulk water, and are oriented with hydrogen atoms closer to nanotube than oxygen.…”
Section: Conclusion: Effect Of Curvature On Energetics Of Benzene Admentioning
confidence: 91%
“…4. As mentioned in the first section (Refs 52, 60 and 61), the structure and dynamics of water molecules confined within CNTs suffered significant changes compared to the bulk phase and hence the interaction nature of optimized system by MD simulation must be considered. Therefore, to simulate a realistic system we have picked up a section of system consisting of water molecules (22H 2 O molecules)/phenylalanine and a piece of nanotube adjacent to the adsorbed molecules which had been equilibrated at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that confined water exhibit sharp increase of pressure inside the nanotubes upon heating and claimed that their scheme could be employed in therapeutic applications of CNTs 60 . Recently, Pérez-Hernández and co-worker systematically investigated the anisotropy effects on the structure and dynamics of water molecules confined within low-diameter CNTs by MD simulation at room temperature 61 . They found that water inside (6, 6) CNT forms frequent chain ruptures by considering anisotropic of the water–carbon interaction while one-dimensional ordered chains was formed in isotropic model.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations have a strong dependency on the force field parameters [18] and DFT lacks a systematic way to improve its performance for the long-range attractive part of the energy [19]. Already in the first theoretical paper about water diffusion inside CNTs, it was noticed that small changes in the nanotube-water interactions can induce large differences in the description of the water load, structure and transport properties [14].…”
Section: Introductionmentioning
confidence: 99%